ATF4-mediated expression of NOXA is critical for necroptosis driven by glucose deprivation - Sonkaew, Sasiprapa; Rajna, Ruwaida; Park, Yeon-Ji; Yan, Jiong; Liu, Zhaoshan; Jitkaew, Siriporn; Liu, Zheng-Gang; Choksi, Swati (Frontiers in Cell Death, 2025)
Glucose deprivation (GD), a common metabolic stress condition, has been recognized as a potent inducer of necroptotic cell death. Our previous findings suggested that the mitochondrial protein, Noxa, may be involved in mediating the release of mitochondrial DNA during GD-induced ZBP1-dependent necroptotic pathway. However, the functional significance of Noxa in necroptosis under GD treatment remains unclear. Here, we investigated the role of Noxa in GD-induced necroptosis and the underlying molecular mechanisms governing its expression. We revealed that Noxa is required for the induction of necroptosis under GD. We also demonstrated that the upregulation of Noxa induced by GD is mediated by ATF4, a key transcription factor. These results provide insights into the regulatory mechanisms underlying Noxa dynamics during GD treatment and highlights its potential as a therapeutic target in cancer therapy and necroptosis-related diseases.